PERAN DAN KOORDINASI LEMBAGA LINTAS SEKTORAL DALAM KONSERVASI SUMBERDAYA AIR (STUDI KASUS DAS GUMBASA KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH) - Muhammad Ansar; Suria Darma Tarigan; Dwi P T Baskoro (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Watershed management consists of multi stakeholders. Therefore, institutional aspect for regulating interaction among stakeholders is very important to be taken into consideration in watershed management. Watershed management will only be efficient if institutional aspect functioning in harmony. Objective of this research is to study role and coordination of cross sectoral government institutions in management of water resource conservation. In this research five elements of water resource conservation were analized, there are: 1) involved organizations, 2) related regulations, 3) management function performance (planning, execution, and controlling), 4) coordination aspect, and 5) priority instrument. Each of those elements was sub-divided into sub-elements according to analysis model used in this research. Two models were used in this analysis. Those are Interpretative Structural Modeling (ISM) and Analytical Hierarchy Process (AHP). Base on the analysis it is concluded that Big Agency of Lore Lindu National Park (BBTNLL), Agency of Watershed Management (BPDAS) Palu-Poso, and Forestry and Plantation Service of Donggala Regency were the most influential organizations in planning, execution, and controlling water resources conservation. Role of those organizations in the management activities were mainly regulated in the respective regulations. Coordination among acting organization is still weak due so the sectoral-ego and lack of qualified human resources.